Kinetic Studies on CO2 Capture using Rubber Seed Shell Activated Carbon - Chan , Sin Wei (IRC, 2016)
Carbon dioxide (CO2) is one of the greenhouse gasses that lead to global warming. The increasing of carbon dioxide emission rate to the atmosphere are mainly due to human activities such as deforestation and burning of fossil fuels. Thus, CO2 capture method using activated carbon is proposed to solve this issue. The main scope of the research is study the effectiveness in using rubber seed shell activated carbon (RSSAC) as an adsorbent for CO2 capture.